Japanese Patients’ and Physicians’ Preferences for Anticoagulant Use in Atrial Fibrillation: Results from a Discrete-choice Experiment - Ken Okumura; Hiroshi Inoue; Masahiro Yasaka; Juan Marcos Gonzalez; A. Brett Hauber; Bennett Levitan; Zhong Yuan; Jean Baptiste Briere (Journal of Health Economics and Outcomes Research)
**Background:** Anticoagulants are recommended for stroke prevention in patients with atrial fibrillation (AF), but are associated with an increased risk of bleeding; therefore, physicians face benefit-risk tradeoffs when prescribing anticoagulants to AF patients. Although the unmet medical need for safer anticoagulants has been well-documented, there is limited information about the importance that patients and physicians place on cardiovascular events.